Proline is not useful as a chemical probe to measure nitrosation in the gastrointestinal tract of patients with gastric disorders characterised by anacidic conditions. Issue 8 (August 1989) - Adam, B; Schlag, P; Friedl, P; Preussmann, R; Eisenbrand, G
Abstract : Aspirated fasting gastric juice from patients with lesions of the gastrointestinal tract and from healthy controls was analysed for nitrite before and after (30, 90, and 240 min) oral administration of 200 mg nitrate. Wilcoxon's rank-sum tests showed no significant differences in fasting gastric juice nitrite concentrations between healthy controls and patients after proximal gastral vagotomy or with gastric/duodenal ulcer (median less than or equal to 0.7 ppm NO-2) and only moderate increases after nitrate administration. Chronic atrophic gastritis patients and patients with Billroth I or II gastric resections showed median concentrations of 2 ppm NO-2 which increased to 20 ppm (up to 200 ppm in one Billroth II patient) after administration of nitrate. Endogenous formation of N-nitrosoproline using the NPRO-test was determined in two groups with low (healthy control and proximal gastral vagotomy patients) and high (Billroth I and II patients) gastric nitrite concentrations. After 12 h fasting, 200 mg nitrate was orally administered, followed 30 min later by 500 mg L-proline. Endogenously formed N-nitrosoproline which is quantitatively excreted in urine was determined in urine over the following 24 hours. In over 80% of the urine samples collected from Billroth I and II patients no detectable NPRO was found whilst in over 85% of the healthy controls and proximal gastral vagotomy patients up to 33.5 micrograms NPRO was detected. In vitro nitrosation kinetics showed that at gastric pH greater than 4 present in both, patients with Billroth I and II resections and with chronic atrophic gastritis, nitrosation of proline does not occur. As alternative chemical probes for quantifying potential endogenous nitrosation in hypoacidic patients the methyl and ethyl esters of proline were investigated. In vivo nitrosation of these two new probes was established in animal experiments using rats and was shown to occur in vitro at pH 4-5. During incubation in human gastric juice, however, almost 30% ester cleavage by non-specific gastric esterases occurred within the first five minutes, thus further limiting the use of these compounds in determining endogenous nitrosation in hypoacidic patients.